2018
DOI: 10.1152/ajpheart.00647.2017
|View full text |Cite
|
Sign up to set email alerts
|

Protection from vascular dysfunction in female rats with chronic stress and depressive symptoms

Abstract: The increasing prevalence and severity of clinical depression are strongly correlated with vascular disease risk, creating a comorbid condition with poor outcomes but demonstrating a sexual disparity whereby female subjects are at lower risk than male subjects for subsequent cardiovascular events. To determine the potential mechanisms responsible for this protection against stress/depression-induced vasculopathy in female subjects, we exposed male, intact female, and ovariectomized (OVX) female lean Zucker rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 58 publications
3
29
1
Order By: Relevance
“…Most of the data presented here were derived from female rats. Although oestrogen has been shown to be protective in certain diseases (Brooks et al 2018b) and beneficial in human health in general, reduced or abolished female protection has been reported in diabetic patients (McCollum et al 2005;Kalyani et al 2014), diabetic rats (He P, Xia X, LaPenna KB & Zhang Y; in press), and in animals with preexisting metabolic diseases (Brooks et al 2018a). In this study, we also found no significant differences in plasma MP concentrations between STZ-induced male and female diabetic rats (Fig.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Most of the data presented here were derived from female rats. Although oestrogen has been shown to be protective in certain diseases (Brooks et al 2018b) and beneficial in human health in general, reduced or abolished female protection has been reported in diabetic patients (McCollum et al 2005;Kalyani et al 2014), diabetic rats (He P, Xia X, LaPenna KB & Zhang Y; in press), and in animals with preexisting metabolic diseases (Brooks et al 2018a). In this study, we also found no significant differences in plasma MP concentrations between STZ-induced male and female diabetic rats (Fig.…”
Section: Discussioncontrasting
confidence: 43%
“…Although oestrogen has been shown to be protective in certain diseases (Brooks et al . b ) and beneficial in human health in general, reduced or abolished female protection has been reported in diabetic patients (McCollum et al . ; Kalyani et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it should be noted that, although not studied, gender/sex hormones might influence finerenone's cardiac and vascular responses to NO and other endothelial autocoids in Zucker fa/fa rats, as observed with other drugs used to reduce cardiovascular risk . Indeed, with pre‐existing metabolic syndrome, female lean Zucker rats are partially protected from the vasculopathy observed in male and ovariectomized female rats, while pre‐existing metabolic syndrome per se provokes impairment of the vasodilator responses to NO and/or prostacyclin; however, whether this will impact finerenone's cardiovascular effects remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
“…As depressioncardiovascular co-morbidity has twice the prevalence in females (Möller-Leimkühler, 2007;Tobet et al, 2013), it is important to consider sex-specific regulation. Interestingly, a recent study investigating vascular function in female rodents after chronic stress actually found that ovarian hormones protect against stress-induced arterial dysfunction (Brooks et al, 2018). Comparing the neural basis of pathological responses in males and females would likely yield a better understanding of the disproportionate female impact of mood disorder-cardiovascular co-morbidity.…”
Section: Discussionmentioning
confidence: 99%